Pengaruh Kecerdasan Emosional terhadap Prestasi Belajar pada Mata Pelajaran Ilmu Pengetahuan Sosial Siswa Kelas VIII SMPN 17 Kota Bekasi - Nurhasanah Nurhasanah (Jurnal Syntax Transformation, 2021)
The corona virus disease pandemic has not only had an impact on the world of health and the economy, but also the world of education. Face-to-face learning activities in schools have been temporarily suspended and replaced with School from home (SFH). This has an impact on the emotional intelligence of students during learning at home (Shool From Home). This research has a function to determine whether there is Emotional Intelligence in the learning achievement of 8th graders (Eighth) in social science subjects at SMPN 17 Bekasi. The research method used in this study is descriptive regression, which is a solution model that seeks the influence of one or more variables. With its variable characteristics, namely the independent variable and the dependent variable. Problem solving in this study uses a quantitative approach that uses statistical tests with the steps of data collection, classification, analysis and data management and making these conclusions. Emotional Intelligence (EQ) is so important in the world of education today, because it affects the achievement and progress of student achievement. Emotional intelligence is a person's ability to manage his emotional life with intelligence (to manage our emotional life with intelligence) maintain emotional harmony and express (the appropriateness of emotion and its pression) through mental awareness skills, mental motivation, empathy, and social skills. Based on the results of research using SPSS (Statistical Product Service Solution) it is known that the multiple linear regression equation is: Y = 59.474 + 0.325 X, so it can be concluded that the hypothesis (Ha) is accepted, the evidence is that there is an influence of emotional intelligence on learning achievement. From the regression equation, it can be interpreted that the regression of 59.474 student achievement (Y) is influenced by an increase in emotional intelligence (X) of 0.325.